The Role of ChatGPT in Student Writing: Opportunities and Challenges in Addressing Plagiarism - Ms.Tayyiba Asim, Ms. Nazma Shaheen, Ms. Atiya Tasneem, Ms. Mahjabeen Mohammed Yousuf (South Eastern European Journal of Public Health, 2025)
The emergence of AI-driven writing tools like ChatGPT has transformed academic writing, making it more efficient and accessible. However, this transformation has also brought up issues regarding academic integrity, specifically plagiarism, and the inadequacy of existing detection systems. This study explores the relationship between the use of ChatGPT and plagiarism in student writing, considering the effects of usage frequency, awareness of academic integrity, and the purpose of application on plagiarism levels. Unlike previous works that focus purely on plagiarism detection or AI ethics, this research touches on how patterns of usage might impact academic integrity, combining a behavioral and technological angle. The theoretical framework used follows a quantitative methodology with ANOVA tests to evaluate the impact of three independent variables—frequency of ChatGPT usage, awareness of academic integrity, and purpose of application—on the dependent variable, plagiarism in student writing. The analysis reflects that students frequently using ChatGPT have increased plagiarism levels as well (F = 8.25, p = 0.003). Students who use this tool for the generation of contents also have increased plagiarism rates substantially (F = 10.68, p = 0.002). But students with awareness of academic integrity scores show significantly less plagiarism rates, (F = 12.47, p = 0.001). It needs stronger ethical guidelines, better academic integrity training, and further developments in the field of AI detection systems. Further research would look into the long-term impact on critical thinking abilities and create methods to achieve both innovation and academic integrity together.